Sistema de monitoramento de barramento CAN de máquinas agrícolas para controle de aplicação de insumos e mapeamento de áreas aplicadas - Rufato, Ewerton César Leme Bersi (2022)
This Course Completion Work aims to use technology to make a system for monitoring the flow of agricultural inputs and mapping the applied areas. Precision Agriculture is a tool of Agriculture 4.0 and allows for the localized management of the crop. In order to make the most opportune management, it is necessary to calculate the production index, which takes place through the integration of the following stages of Precision Agriculture: intensive monitoring, generation and integration of maps, systematization of agronomic modeling, and differentiated application of inputs in the place, time and quantities required. This system monitors the flow using the CAN bus of agricultural equipment and provides maps and graphics of production input application. The farm operation operator is alerted as programmed. A configuration interface was built, that allows the operator to control variables of interest, for example, target application rate, tolerance, flow unit, and add a phone number to receive alerts. Trace maps and graphs were prepared to allow an analysis of the operation. This embedded system prototype is substantially composed of a CAN transceiver TJA1050, which communicates with the physical bus, an ESP32 DevKit V1 as a processing module, a GSM GPRS SIM800L module for sending and receiving SMS/phone calls, a GPS receiver NEO-6M for obtaining geographic coordinates, and an SD card. With the report available on the SD card, it is possible to obtain the application map that allows visualization of altitude, machine speed, date and time, route traveled (machine trail), and input flow during the route. The installation instructions and the programs necessary to use this system are available in appendix Q. The results obtained demonstrate that the implemented system is suitable and can be used for applications in different machines as long as they have an automotive CAN protocol.